Trends in Prescribing Systemic Antibiotics by Libyan Dentists and Periodontists - Ghadah Elhassy; Nesrin El-Naihoum (AlQalam Journal of Medical and Applied Sciences, 2024)
Antibiotic prescription is a common practice in everyday dentistry. Although antibiotics play a crucial role in managing periodontal disease, the threat of antibiotic resistance is an issue that requires more exploration. The aim of this study was to describe the patterns of prescribing systemic antibiotics treating periodontal and peri-implant diseases among Libyan dentists and periodontists. An online cross-sectional survey was designed to investigate the patterns and perspectives of antibiotic prescription. Indication parameters and timing of prescription that were analysed included: chronic gingivitis, chronic periodontitis, aggressive periodontitis, acute gingival and periodontal conditions, periodontal surgery, implant placement surgery, peri-implantitis treatment, and antibiotic prophylaxis for infective endocarditis. Out of the 3000 registered Libyan dentists, only 181 participated in the study. Systemic antibiotic prescription patterns varied markedly for different periodontal or peri-implant diseases among respondents. 72.29% of the respondents reported prescribing systemic antibiotics for the treatment of aggressive periodontitis, while 34.93% prescribed them for chronic periodontitis, 10.24% for chronic gingivitis, 71.15% for periodontal surgery, 64.64% for implant placement surgery, and 67.95% for peri-implanttitis treatment. The most commonly prescribed systemic antibiotics were amoxicillin, the combination of amoxicillin with metronidazole, and clavulanate potassium. This study revealed a high prevalence of overuse and misuse of systemic antibiotics in dental practice. Furthermore, it emphasizes the necessity of improving antimicrobial resistance awareness among Libyan dentists and incorporating antimicrobial stewardship. وصف المضادات الحيوية ممارسة شائعة في طب الأسنان اليومي. على الرغم من أن المضادات الحيوية تلعب دورًا حاسمًا في علاج أمراض اللثة و دواعم الأسنان وحول الزرعات السنية، فإن تهديد مقاومة المضادات الحيوية هو قضية تتطلب المزيد من الاستكشاف. تهدف هذه الدراسة إلى وصف أنماط وصف المضادات الحيوية الجهازية لعلاج أمراض وحالات اللثة و دواعم الأسنان وحول الزرعات السنية بين أطباء الأسنان وأخصائيي أمراض وعلاج اللثة الليبيين. تم تصميم دراسة استقصائية مقطعية عبر الإنترنت للتحقيق في أنماط ووجهات النظر في وصف المضادات الحيوية. وشملت معايير المؤشرات وتوقيت الوصف التي تم تحليلها: إلتهاب اللثة المزمن، إلتهاب دواعم السن المزمن، التهاب دواعم السن العدواني، التهابات اللثة و دواعم السن الحادة، جراحة اللثة ودواعم الأسنان، جراحة وضع الزرعات السنية، علاج إلتهاب محيط الغرسة، والوقاية بالمضادات الحيوية لإلتهاب الشغاف المعدي. ومن بين 3000 طبيب أسنان ليبي مسجل، شارك 181 طبيبًا فقط في الدراسة. وتباينت أنماط وصف المضادات الحيوية الجهازية بشكل ملحوظ بين المستجيبين. وأفاد 72.29٪ من المستجيبين بوصف المضادات الحيوية الجهازية لعلاج إلتهاب دواعم السن العدواني، بينما وصفها 34.93٪ لإلتهاب دواعم السن المزمن، و10.24٪ لإلتهاب اللثة المزمن، و71.15٪ لجراحة اللثة ودواعم السن، و64.64٪ لجراحة وضع الزرعة السنية، و67.95٪ لعلاج إلتهاب محيط الزرعة السنية. كانت المضادات الحيوية الجهازية الأكثر وصفًا هي الأموكسيسيلين، ومزيج الأموكسيسيلين مع الميترونيدازول، ومزيج الأموكسيسيلين وكلافولانات البوتاسيوم. كشفت هذه الدراسة عن انتشار كبير للاستخدام المفرط للمضادات الحيوية الجهازية وإساءة استخدامها في ممارسة طب الأسنان. وعلاوة على ذلك، تؤكد على ضرورة تحسين الوعي بمقاومة مضادات الميكروبات بين أطباء الأسنان الليبيين ودمج إدارة مضادات الميكروبات